Tongue shaped oropharyngeal teratoma with cleft palate in a neonate: A case report - Hasan, Samiul; Afroz, Nadia; Reza, Jiaul (Journal of Neonatal Surgery, 2021)
Background: Atypical presentation of an atypical abnormality makes the diagnosis challenging. Oropharyngeal teratoma (epignathus) is a rare, potentially life-threatening neonatal tumor. Its atypical presentation may cause a delay in diagnosis and increase morbidity and mortality. Case presentation: A newborn girl with oropharyngeal teratoma and cleft palate presented with feeding difficulty. The airway was patent. The tumor was tongue-shaped, smooth-walled, displacing the native tongue, and prevented the fusion of two palatine halves resulting in cleft palate. On the 4th day of life, complete excision was done transorally. Histopathology revealed a mature teratoma. There was no sign of recurrence at three months of follow-up. Conclusion: Presentation of the oropharyngeal teratoma varies according to its site, size, and extension. Timely diagnosis is essential to avoid life-threatening respiratory obstruction. Complete excision of the mass is usually associated with a good prognosis.